2007
DOI: 10.1152/ajpcell.00596.2006
|View full text |Cite
|
Sign up to set email alerts
|

Relocalization of the V-ATPase B2 subunit to the apical membrane of epididymal clear cells of mice deficient in the B1 subunit

Abstract: Ϫ/Ϫ mice do not develop metabolic acidosis and are fertile. While B1 is located in the apical membrane of narrow and clear cells, the B2 subunit localizes to subapical vesicles in wild-type mouse, rat and human epididymis. However, a marked increase (84%) in the mean pixel intensity of B2 staining was observed in the apical pole of clear cells by conventional immunofluorescence, and relocalization into their apical membrane was detected by confocal microscopy in B1 Ϫ/Ϫ mice compared with B1 ϩ/ϩ . Immunogold el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 61 publications
3
44
0
2
Order By: Relevance
“…Immunogold electron microscopy was performed to localize the V-ATPase, as we have previously described (2,15,57). Small pieces of PLP-fixed epididymis were embedded at Ϫ45°C using HM20 resin (Electron Microscopy Sciences) in a Leica EM AFS, and then ultrathin sections were cut using a Leica Ultracut EM UC7 ultramicrotome (Leica Microsystems, Bannockburn, IL) and collected on Formvar-coated, gilded nickel grids.…”
Section: Methodsmentioning
confidence: 99%
“…Immunogold electron microscopy was performed to localize the V-ATPase, as we have previously described (2,15,57). Small pieces of PLP-fixed epididymis were embedded at Ϫ45°C using HM20 resin (Electron Microscopy Sciences) in a Leica EM AFS, and then ultrathin sections were cut using a Leica Ultracut EM UC7 ultramicrotome (Leica Microsystems, Bannockburn, IL) and collected on Formvar-coated, gilded nickel grids.…”
Section: Methodsmentioning
confidence: 99%
“…Differential expression of a particular set of isoforms in different cell types controls the sub-cellular localization of the V-ATPase holo-enzyme (Hurtado-Lorenzo et al, 2006;Kawasaki-Nishi et al, 2001a;Kawasaki-Nishi et al, 2001b;Pietrement et al, 2006;Sun-Wada et al, 2003;Sun-Wada et al, 2004;Toyomura et al, 2003). In the epididymis, subunits A, B1, B2, C1, C2, G1, G3, E, a1, a4, d1 and d2 are all enriched in the apical domain of narrow and clear cells (Da Silva et al, 2007a;Paunescu et al, 2004;Pietrement et al, 2006). In addition, subunits A and a2 were detected in intracellular structures closely associated with the trans-Golgi network of all epithelial cells (Pietrement et al, 2006).…”
Section: Clear Cells Express the V-atpase In Their Apical Membranementioning
confidence: 97%
“…Such isoform replacement occurs in the absence of B1 in B1-knockout (KO) mice, where the compensatory insertion of B2 with the plasma membrane-bound V-ATPase allows VATPase-dependent proton transport to occur across the membrane of epididymal clear cells and renal intercalated cells (Da Silva et al, 2007a;Paunescu et al, 2007). Accordingly, male mice lacking the B1 subunit do not develop dRTA and are not infertile (Da Silva et al, 2007a). By contrast, in humans harboring B1 mutations, B2 replacement does not appear to take place, which results in the development of dRTA.…”
Section: V-atpase Isoform Compensatory Functionmentioning
confidence: 99%
“…It is unlikely that these effects are due to abnormal metabolism through phloretin's inhibition of glucose transport via the glucose transporter, since the BWW medium contains the respiratory substrates lactate and pyuvuate. Although phloretin can inhibit AQP9 (Castle 2005), where antibodies have been used on epididymal sections, there are no reports of this AQP in luminal spermatozoa (Ruz et al 2006, Da Silva et al 2007. Experiments designed to determine the possible alternative RVD mechanism in the presence of quinine and phloretin, leading to the observed water efflux, showed that both TEA and furosemide were able, in the same animals, to delay the onset of RVD.…”
Section: Discussionmentioning
confidence: 99%